RELATIONSHIP BETWEEN LEARNING MOTIVATION TO LEARNING ACHIEVEMENT AMONG MIDWIFERY STUDENTS IN IN ‘AISYIYAH UNIVERSITY YOGYAKARTA, INDONESIA - Jusmala Sari; Lilik Hartati; Novita Puspita Dewi; Isti Chana Zuliyati (Proceedings of the International Conference on Applied Science and Health, 2017)
Background: Teaching and learning is a process of conscious purpose. Goals can be informed an attempt to give students the formulation of the expected results after implementing a learning. High-performance students have a good indication to their knowledge. One of the factors that affect student achievement is motivation. The motivation will make students study harder,tenacious, diligent and have full of concentration in teaching and learning. Encouragement in education is one thing that needs to inform to learning in school. Aims: The purpose of this study was to seek the relationship between learning motivation to learning achievement among midwifery students in Universitas 'Aisyiyah Yogyakarta. Methods: It was an analytical study with cross-regional approach. A total of 122 students, invited from the two classes of Diploma IV Program of Universitas 'Aisyiyah Yogyakarta, was selected using proportional random sampling. A questionnaire related to students’ motivation and performance was used. The collected data was then analyzed by Spearman test. Results: By the data analysis, we highlight a significant relationship between learning motivation and academic performance in the subjected population (p value < 0.001). Conclusion: The finding alarms a need to pay attention to what can motivate the students to be involved in learning activity. Motivation is one of the key factors to reach high academic performance in Diploma IV Program of Universitas 'Aisyiyah Yogyakarta, Indonesia.